Studi Deskriptif Karya Kolase dari Bahan Alam Pada Pembelajaran SBDP Kelas II SDIT Al Hasanah 1 Kota Bengkulu - Munawir, Ischak; Kurniawati, Ike (Universitas Bengkulu, 2024)
This study aims to describe the process of making works and the results of collage works from natural materials in SBdP learning for class 2B students of SDIT Al Hasanah 1, Bengkulu City. The type of research is qualitative research with descriptive methods. The data collection method is descriptive qualitative. Data collection techniques are observation, interviews and documentation. The research instruments are observation sheets, interview guidelines and documentation tables. As for describing the results of the work in this study, the researcher is guided by the table of elements and principles of fine art. Qualitative data analysis was carried out simultaneously with the data collection process, namely during and after data collection. The collage work of Class 2B students of SDIT Al Hasanah 1 has artistic value because it has elements and principles of fine art. The activity of making collages is a combination of several activities that use fine motor skills of the hands. For drawing, cutting, sticking, and coloring skills, teachers are advised to increase activities in SBDP learning and integrate them into other learning. Students' collage works that are made with the right steps and have elements of art and a sense of fine art are works of art that have educational, recreational and inspiring functions. Educational because it is a means of learning for students at school. Recreational because it has a pleasing beauty to the eye. And inspiring because it can motivate others, especially students, to create similar or even better works.